Palynomorphological peculiarities of representatives of tribes Lindenbergieae and Cymbarieae and pollen evolution in early-branching lineages of Orobanchaceae - Tsymbalyuk, Z.M.; Mosyakin, S.L. (Український ботанічний журнал, 2018)
Pollen morphology of four species belonging to four genera of the tribe Cymbarieae and two species of Lindenbergia of the tribe Lindenbergieae (Orobanchaceae) was studied using light and scanning electron microscopy. Pollen grains in Lindenbergieae are 3-colporate (rarely 2-colporate), prolate, spheroidal and oblate-spheroidal, small-sized, with reticulate exine sculpture. Pollen grains in Cymbarieae are 3-colpate, rarely 4-colpate, prolate, spheroidal and oblate-spheroidal, medium-sized. Exine sculpture in Cymbarieae is retipilate and rugulate-retipilate. Pollen characters of Cymbarieae and Lindenbergieae are compared with pollen patterns in Paulowniaceae and crown clades of Orobanchaceae. The earliest-branching clade of Orobanchaceae (Lindenbergieae) is palynomorphologically similar to Paulowniaceae (the clade sister to all Orobanchaceae) and to Wightia. These palynomorphological findings confirm the phylogenetic patterns recently revealed in basal Orobanchaceae and their closest relatives. It is concluded that the colporate (most probably 3-colporate) type of pollen grains could be ancestral in Orobanchaceae. Pollen diversity in crown clades of Orobanchaceae evolved on the base of a few pollen types and subtypes, which were peculiar to hypothetical ancestors of Orobanchaceae and are probably preserved in the extant taxa of Paulowniaceae and Lindenbergieae.